Obstetric and Gynecologic Departments, Faculty of Medicine Udayana University, Bali-Indonesia - Mahendra-Dewi, I G. A. S.; Suwiyoga,; I K. (Udayana University, 2013)
The high risk of human papillomavirus (HPV) have already known widely and accepted as a causative agent for cervical cancer. Epidemiologically, predominant high-risk is HPV-16 and squamous cell carcinomas (SCC) is the most common histological type. HPV genotype probably correlates to histologic type. This study aims to determine how many fold is the risk of SCC on HPV-16 infection. This is a case control with SCC HPV-16 positive as the cases and SCC HPV-16 negative as the controls. Tissues diagnosed as SCC and non SCC was paraffin-embedded. SPF-10 and specific E7-primer types by LiPA were employed for genotyping of HPV-16. c2 was applied to analyze the correlation. A number of 65 SCC consisted of 33 cases and 32 controls were observed in this study. The risk of SCC on HPV-16 infection was 3.40-fold (95% CI = 1.44-8.03; p = 0.004) compare with HPV-16 negative. Controls in this study consist of 18 (27.69%) of HPV-18, 9 (13.85%) of HPV-52, and 5 (7.69%) of other HPV types. The mean-age of case group and control group infected by HPV were 52.28 ± 12.43 and 47.70 ± 8.02 year, respectively (p = 0.02). HPV-16 infection caused SCC is 3.5 more than other high risk group.